DNA hypermethylation of MAL gene may act as an independent predictor of favorable prognosis in patients with colorectal cancer - Liu, Xinyan; Bi, Haoran; Ge, Anqi; Xia, Tingting; Fu, Jinming; Liu, Yupeng; Sun, Hongru; Li, Dapeng; Zhao, Yashuang (Translational Cancer Research; Vol 8, No 5 (September 30, 2019): Translational Cancer Research, 2019)
Background: Aberrant DNA methylation could be used as biomarkers for colorectal cancer (CRC) detection and assessment of prognosis. The aim of our study was to investigate the potential possibility of MAL methylation as a prognostic biomarker for postoperative CRC patients. Methods: We followed up 298 sporadic postoperative CRC patients and detected MAL methylation in tumor tissues and adjacent non-tumor tissues by methylation-sensitive high resolution melting (MS-HRM) analysis. Univariate, multivariate Cox regressions were performed to evaluate the potential possibility of MAL methylation as a predictor of prognosis. Propensity score (PS) analysis was used to control confounders. Results: The MAL methylation level in adjacent non-tumor tissues was significantly lower than that in tumor tissues (P